ANALISIS LAJU PERUBAHAN TUTUPAN LAHAN DI KABUPATEN SINJAI SECARA TEMPORAL - Muhlis Muhlis; Fatmawati Fatmawati; Sappewali; Muhtar Muhtar; Rakhmad Armus; C. Selry Tanry (Universitas Pahlawan Tuanku Tambusai, 2022)
Land cover change is a major problem with environmental sustainability. The impact of the increasing population is urgent for the need for land for human activities. The purpose of this study is to determine the magnitude of land cover changes that occur in Sinjai Regency for the period 2014 to 2022. The research uses quantitative research. That is research that starts from a specific plan or a detailed set of questions or hypotheses. This research is closely related to the process of enumerative induction (induction based on calculations). Based on the analysis using imagery data, the rate of land change in Sinjai district was obtained as follows: : land cover in the form of mixed land decreased by 287.61 Ha, secondary forest decreased by 135.98 Ha, primary forest by 20.04 Ha, water body by 140.46 Ha and other uses increased by 586.53 Ha. Keywords: rate of change, land cover, temporal